Provenance of the sedimentary rocks of the Bom Jardim Group (Neoproterozoic, Southern Brazil): Evidence from petrography, geochemistry and neodymium isotopes (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Provenance studies are helpful in reconstructing the tectonic, climatic and geographic setting of terrigenous sedimentary basins. The primary controls on the composition of detrital sedimentary rocks are the composition, climate and relief conditions of the source areas, the transport mechanisms, and diagenesis. In order to constrain the provenance of the Neoproterozoic (ca. 600 - 580 Ma) sedimentary rocks of the Bom Jardim Group (Arroio dos Nobres Formation) in the Lavras do Sul (west), Bom Jardim (central) and Cerro da Árvore (east) areas, petrography, major and trace element geochemistry, and Nd isotopic data were analyzed together. The results indicate a clear lateral variation of provenance parameters. In the region of Lavras do Sul, near syn-sedimentary volcanic rocks of shoshonitic affinity (the Hilário Formation), the sandstones are epiclastic, plotting in the undissected and transitional arc fields of the QFL diagram, display relatively higher values of Na, Ba, Sr and Zr, and yield a 143Nd/144Nd ratio of 0.512263 and present-day ?Nd of -7.32. In the Bom Jardim area, east of Caçapava do Sul, the sedimentary rocks are also dominated by volcanic fragments, but display significant values of metamorphic detritus. The relatively higher values of Cr, Co and Ni suggest some contribution of ophiolitic or lamprophyric source areas, while the 143Nd/144Nd ratio is 0.511906 and the ?Nd(0) is around -14.28. In the easternmost outcropping area, the Cerro da Árvore (or Piquiri) region, the sedimentary rocks are rich in metasedimentary clasts, with significant amounts of polycrystalline quartz fragments, plotting in the orogenic recycling field. Comparatively, the value of the K2O/Na2O ratio is higher, the 143Nd/144Nd ratio is 0.511887 and the ?Nd(0) is of -14.65, suggesting older and more acidic source rocks, probably constituents of the Porongos metamorphic complex.
Keywords: Neoproterozoic; Bom Jardim Group; Sedimentary rocks; Provenance; Nd isotopes